Climate Change and Community Perceptions in the Khudi Watershed, Lamjung, Nepal - Sharma, Aseem Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Climate change and people’s perception on such changes are analysed for the Khudi Watershed in Western Nepal. Climate change trends in the western hilly region of Nepal were investigated focusing on two major climatic indicators: surface air temperature and rainfall. Further, community’s perceptions on climate change impacts were analysed. We found considerable warming in the study area with a mean temperature increase of 0.18°C decade-1. Annual rainfall is varying with prolonged dry periods. During monsoon season short but intense rainfall events were observed. Local denizens have also experienced these changes and think that weather related changes are affecting their livelihood practices with increased weather related disasters, less agricultural yield, and imbalances in socio-economic behavior. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 17, July 2015